Redesigning global supply chains during compounding geopolitical disruptions: the role of supply chain logics - Roscoe, Samuel; Aktas, Emel; Petersen, Ken; Skipworth, Heather; Handfield, Robert B.; Habib, Farooq (Emerald, 2022)
Purpose: Why do managers redesign global supply chains in a particular manner when faced with compounding geopolitical disruptions? In answering this research question, our study identifies a constrained system of reasoning (decision-making logic) employed by managers when they redesign their supply chains in situations of heightened uncertainty. Design/methodology/approach: We conducted 40 elite interviews with senior supply chain executives in 28 companies across nine industries from November 2019 to June 2020, when the United Kingdom was preparing to leave the European Union, the US-China trade war was escalating, and Covid-19 was spreading rapidly around the globe. Findings: When redesigning global supply chains, we find that managerial decision-making logic is constrained by three distinct environmental ecosystem conditions: 1) the perceived intensity of institutional pressures; 2) the relative mobility of suppliers and supply chain assets, and; 3) the perceived severity of the potential disruption risk. Intense government pressure and persistent geopolitical risk tend to impact firms in the same industry, resulting in similar approaches to decision-making regarding supply chain design. However, where suppliers are relatively immobile and supply chain assets are relatively fixed, a dominant logic is consistently present. Originality/value: Building on an institutional logics perspective, our study finds that managerial decision-making under heightened uncertainty is not solely guided by institutional pressures but also by perceptions of the risk of supply chain disruption and immobility of supply chain assets. These findings support the theoretical development of a novel construct that we term ‘supply chain logics.’ Finally, our study provides a decision-making framework for Senior Executives competing in an increasingly complex and unstable business environment.
Keywords: Covid-19; Brexit; US-China trade war; strategy development; institutional theory; supply chain design; supply chain logics